FORMULASI KEBIJAKAN PERLINDUNGAN ANAK DI KOTA SEMARANG - Sewitra Bagaskara; Dyah Lituhayu (Journal of Public Policy and Management Review, 2017)
Child protection is one of the policies that are passed by government as an attempt to protect children from sets of problems. In the city of Semarang, most of the problems arise within children are psychological and physical violence. Over the year, the number of child violence cases that happen in Semarang keep on increasing and was the highest in Central Java. Children have important roles and positions for the future of the Semarang. Therefore, children have the rights to grow and develop optimally. Child protection policy in Semarang was passed in 2016 after facing many obstacles previously. This research will further elaborate the process of child protection formulation policy in Semarang.The results of this research show that the formulation of child protection policy Semarang had problems that were related to miss-coordination between legislative with executive, which resulted in the delay of the policy being finalized. The other factor that obstructed the policy making was the fact that people do not care about child protection in Semarang. Recommendations earned from this research are; to increase the coordination between legislative and executive so that there will not be mistakes in the distribution of tasks—so that maximum outcome can be reached, and to increase the work quality of Pusat Pelayanan Terpadu. It is also very important to build a good, solid teamwork between the government and citizens to decrease the child violence level in Semarang.